1997
DOI: 10.1152/jn.1997.78.4.2079
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Selectivity of Mechanically Activated Channels in Spider Mechanoreceptor Neurons

Abstract: The lyriform slit-sense organ on the patella of the spider, Cupiennius salei, consists of seven or eight slits, with each slit innervated by a pair of mechanically sensitive neurons. Mechanotransduction is believed to occur at the tips of the dendrites, which are surrounded by a Na+-rich receptor lymph. We studied the ionic basis of sensory transduction in these neurons by voltage-clamp measurement of the receptor current, replacement of extracellular cations, and application of specific blocking agents. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 32 publications
3
68
0
Order By: Relevance
“…The second major type of mechanosensitive current inactivates very rapidly but, like the slowly adapting current, has a very short latency and a fast activation time constant . Interestingly, like the mechanoreceptor current analyzed in invertebrates (Hoger et al 1997;O'Hagan et al 2005), the rapidly adapting mechanosensitive current is also relatively selective for sodium ions . It has long been known that in vivo the time taken for a suprathreshold mechanical stimulus to initiate a spike in an individual mechanoreceptor can be in the order of a millisecond or less (Bell et al 1994).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The second major type of mechanosensitive current inactivates very rapidly but, like the slowly adapting current, has a very short latency and a fast activation time constant . Interestingly, like the mechanoreceptor current analyzed in invertebrates (Hoger et al 1997;O'Hagan et al 2005), the rapidly adapting mechanosensitive current is also relatively selective for sodium ions . It has long been known that in vivo the time taken for a suprathreshold mechanical stimulus to initiate a spike in an individual mechanoreceptor can be in the order of a millisecond or less (Bell et al 1994).…”
Section: Introductionmentioning
confidence: 93%
“…The underlying mechanosensitive ion channels are thought to be largely voltage insensitive and their activation under normal physiological conditions leads to a graded receptor potential . Electrophysiological investigations of transduction events in vivo using intracellular recording techniques have been successfully carried out in spider slit organ mechanoreceptors and more recently in nematode body touch receptors (Hoger et al 1997;O'Hagan et al 2005). These studies have shown that, at least in invertebrates, some mechanosensitive ion channels are relatively sodium selective and insensitive to membrane voltage.…”
Section: Introductionmentioning
confidence: 99%
“…For current-and voltage-clamp experiments a "hypodermis preparation" was used: the hypodermis membrane was detached from the cuticle with the VS-3 neurons attached and placed on a poly-L-lysine (1 mg/ml) coated coverslip in a recording chamber as described previously (Sekizawa et al 1999). Preparations were continuously superfused with spider saline [in mM: 223 NaCl, 6.8 KCl, 8 CaCl 2 , 5.1 MgCl 2 , 5 sucrose, and 10 HEPES, pH 7.8 (Höger et al 1997)]. All chemicals were purchased from Sigma (Oakville, ON, Canada) if not otherwise indicated.…”
Section: Experimental Animals and Preparationsmentioning
confidence: 99%
“…The hypodermis membrane with the VS-3 slit sense organ was detached from the cuticle and attached to a coverslip coated with 1 mg/ml poly-L-lysine (Sigma P5899) and then placed in a recording chamber as described previously in detail (Sekizawa et al 1999). The preparation was superfused continuously with spider saline [in mM: 223 NaCl, 6.8 KCl, 8 CaCl 2 , 5.1 MgCl 2 , 5 sucrose, and 10 HEPES, pH 7.8 (Höger et al 1997)] using a BPS-4 solution exchange system and PR10 pressure regulator (ALA Scientific, New York, NY). The drugs were injected either using the solution exchange system or manually with a syringe and a needle.…”
Section: Electrophysiologymentioning
confidence: 99%